Worldviews: Competing perceptions of the world - Mona Kanwal Sheikh (Danish Institute for International Studies (DIIS), 2022)
In a DIIS Working Paper that summarizes earlier contributions, Mona Kanwal Sheikh describes the development in her work on worldview analysis. She has worked on two intertwined concepts and frameworks for thinking; first sociotheology (Juergensmeyer & Sheikh 2013) and secondly worldviews (Sheikh, 2018; Sheikh and Juergensmeyer 2019). While the first was initially an identification of a scholarly approach that integrates theology and social sciences, the second collaboration developed into a methodological elaboration of how scholars can embrace an insider-oriented understanding of how their religious research subjects view the world, published in the volume Entering Religious Minds - The Social Study of Worldviews (2019). The approach to worldview analysis outlined here is based on the dissolvement of dichotomies between inside-outside, mind-body, rationalities-emotions, and highlights the social dimension of worldviews and its significance for conflict analysis. The paper is part of the Worldview Initiative at DIIS coordinated collaboratively by Lars Erslev Andersen and Mona Kanwal Sheikh. It is part of a series of papers on the concept of worldviews, and among others based on a workshop with scholars and practitioners from the mediation field convened in collaboration with Harvard University.
Keywords: 330